2021
DOI: 10.1088/1361-6463/abd20e
|View full text |Cite
|
Sign up to set email alerts
|

Atomic oxygen generation in atmospheric pressure RF plasma jets driven by tailored voltage waveforms in mixtures of He and O2

Abstract: Absolute atomic oxygen densities measured space resolved in the active plasma volume of a COST microplasma reference jet operated in He/O2 and driven by tailored voltage waveforms are presented. The measurements are performed for different shapes of the driving voltage waveform, oxygen admixture concentrations, and peak-to-peak voltages. Peaks- and valleys-waveforms constructed based on different numbers of consecutive harmonics, N, of the fundamental frequency f 0 = 13.56 MHz, different rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 101 publications
1
36
0
1
Order By: Relevance
“…[ 30,41 ] Electron impact excitation of ground‐state molecular and atomic oxygen leads to the emission at 844.6 and 777.4 nm, which is predicted by the dissociative excitation, given as, e+normalO2e+normalO*+O and direct impact excitation mechanisms, e+Oe+normalO*, where O * refers to the O (3p 5 P) state, which emits at 777.4 nm, and the O (3p 3 P) state, which emits at 844.6 nm. [ 48–50 ] The generation of oxygen metastable is predominantly caused by electron impact dissociation of O 2 , and electron‐induced processes dominate the generation of ground‐state atomic oxygen. The formation of such intense reactive species in helium discharge is beneficial for atmospheric pressure plasma applications, especially for biomedical treatment and plasma processing.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30,41 ] Electron impact excitation of ground‐state molecular and atomic oxygen leads to the emission at 844.6 and 777.4 nm, which is predicted by the dissociative excitation, given as, e+normalO2e+normalO*+O and direct impact excitation mechanisms, e+Oe+normalO*, where O * refers to the O (3p 5 P) state, which emits at 777.4 nm, and the O (3p 3 P) state, which emits at 844.6 nm. [ 48–50 ] The generation of oxygen metastable is predominantly caused by electron impact dissociation of O 2 , and electron‐induced processes dominate the generation of ground‐state atomic oxygen. The formation of such intense reactive species in helium discharge is beneficial for atmospheric pressure plasma applications, especially for biomedical treatment and plasma processing.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma Control: Control over plasma composition is mandatory for a targeted medical application. Tremendous progress has been made in controlling electron dynamics, e.g., through a multifrequency approach [44]. Ensuring a reproducible composition by using a tailored gas surrounding the active effluent has opened the door to several promising fundamental biomedical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicated that the addition of small amounts of oxygen (O 2 ) to the gas employed to produce plasma, usually argon (Ar) or helium (He), can increase the amount of atomic oxygen (O) produced in the APPJ [11][12][13][14][15][16][17]. To verify this increase in the population of O most authors have measured the light emission from excited O atoms coming from the 777 nm triplet or, in some cases, from the 844 nm triplet [13].…”
Section: Introductionmentioning
confidence: 99%